Study on Synthesis, Characterization and Antituberculosis Activity of Biologically Nanostructured Zinc and Titanium Metal Compounds - Savita Belwal; Sujana Kariveda; Saritha Ramagiri (New Innovations in Chemistry and Biochemistry Vol. 5, 2021)
Green chemistry was used to obtain nano-range sized titanium and zinc compounds from their macro-sizes by using an aqueous extract of horse gram (Macrotyloma uniflorum). Green technology allows the transformation of metal ions into metal nanoparticles through inherent biochemical processes. Ultraviolet-visible (UV-vis) and Fourier-transform infrared (FTIR) spectrophotometers were employed for characterizing the nanoparticles of biosynthesized metal nanoparticles. Transmission electron microscopy (TEM) was used to analyse the reduced nanoparticles of Ti and Zn metals. Micro dilution was employed to determine in vitro properties, such as effects of nano complex antimicrobials on Mycobacterium tuberculosis (MTB) H37RV strain. MTB strains isolated from patients with multidrug-resistant tuberculosis (MDR-TB) were resistant to first-line drugs. Novel synthesized nano-complexes exhibited potential antituberculosis activities. Titanium nano complexes exhibited the highest minimal inhibitory concentration (MIC) in comparison to zinc nano complex. In a cytotoxic study, an IC50 of 1000 µg/mL, for both Ti and Zn nano complexes, was reported, and thus, these complexes were non-toxic when compared to isoniazid.